Effect of Training Program on Knowledge and Practice of Breast feeding Women During COVID-19 - Amnah M. Harthi MD; Abeer M. Harthi BSc; Abdelaziz Hendy MD (SAGE Publishing, 2023)
Aim Evaluate the effect of the training program on knowledge and practice of breastfeeding women during coronavirus disease 2019 (COVID-19). Methods One-group pretest/post-test quasiexperimental research design was utilized to accomplish the aim of this study. The study was carried out at the primary health care units Ad Dar Al Baida 1, Ad Dar Al Baida 2, Al Aziziyah at Riyadh Province of Saudi Arabia. The study included a convenience sample of 100 breastfeeding women. Tool A structured interviewing questionnaire sheet was used for data collection that included three parts knowledge, reported practice, and demographic characteristics. Results More than one-quarter (30%) and (28%) of studied women had satisfactory knowledge-related causes, risk factor and signs, symptoms of COVID-19 at preintervention, while the majority 85% and 86% of them had satisfactory knowledge postintervention at p -value <.01**. In addition, less than one-fifth (17%) and (16%) of studied women had satisfactory knowledge about Breastfeeding guidelines during COVID-19 and care of breastfeeding women during COVID-19, compared with most of them (89%) and (92%) postintervention at p -value <.01**. Conclusion Based on our current study, it was concluded that the educational program effectively improves breastfeeding women's knowledge and practices. There was a highly statistically significant positive linear correlation between the breastfeeding women's knowledge and reported practices regarding COVID-19 infection before and after the implementation of the educational program at p  < .0.